A Methodology to Assess Increased Storage Capacity Provided by Fracture Networks at CO2 Storage Sites: Application to in Salah Storage Site - Smith,J; Durucan,S; Korre,A; Shi,J (Energy Procedia, 2013)
The presence of fractures in the storage reservoir at CO2 storage sites may increase the reservoir permeability and subsequently cause the CO2 plume extent to increase. Similarly, fractures in the caprock could provide regions of secondary storage if CO2 escapes from the reservoir. An important factor influencing the degree of these effects is whether the fractures form a continuously connected, or percolating, pathway. A methodology assessing the existence of percolating network of fractures, which incorporates the uncertainties in measured fracture properties around wells, was applied to assess secondary storage in the lower caprock at the In Salah Storage Site. It is demonstrated that secondary storage will occur if the fracture line density is equal to or greater than 2 m-1 and further shown what length distributions will provide secondary storage, if line density is less than 2 m-1.